Effect of whole body vibration on spasticity in hemiplegic legs of patients with stroke. Issue 2 (17th February 2018) - Miyara, Kodai; Matsumoto, Shuji; Uema, Tomohiro; Noma, Tomokazu; Ikeda, Keiko; Ohwatashi, Akihiko; Kiyama, Ryoji; Shimodozono, Megumi
Abstract: Background: Several reports have focused on the effects of whole body vibration (WBV) on spasticity with differing results. Most studies used modified Ashworth scale (MAS) for qualitative measurements, but the effect was small. Objective: To investigate the effect of WBV on spasticity in hemiplegic legs of patients with stroke using F -wave parameters. Methods: Sixteen patients with stroke (mean age, 54.7 ± 13.5 years: time after stroke, 28.0 ± 26.3 months) were enrolled in a comparative before-and-after intervention trial. WBV was applied at 30 Hz (4–8 mm amplitude) for 5 min on the hamstrings, gastrocnemius, and soleus muscles in a sitting position. Spasticity was assessed according to the F -wave parameters, MAS, and active and passive range of motion (A-ROM and P-ROM, respectively). These assessments were obtained before, immediately after, and 20 min after each intervention. Results: The F -wave parameters, MAS score, and P-ROM improved significantly after the WBV and remained below the baseline level, even after 20 min; no such change was noted in the unaffected limb via the F -wave parameters. The WBV also improved volitional movement immediately after intervention, as indicated by the A-ROM. Conclusions: These results confirmed a significant reduction of motor neuron excitability until 20 min after the WBV, as indicated by F -wave parameters.